Optimum Design of the Electricity System on Nusa Penida Island With Utilization of Renewable Energy - Sugma Wily Supala; Tajuddin Nur; Joko Muslim (Journal of Social Research, 2025)
Nusa Penida is an island that located near the Bali. This island is part of Klungkung Regency, Bali, Indonesia, that located at southeast of Bali and separated by the Badung Strait. Nusa Penida is close to other small islands such as Nusa Ceningan and Nusa Lembongan. Nusa Penida is famous as a tourist spot such as Crystal Bay, Manta Point, Batu Meling, Batu Lumbung, Batu Abah, Toyapakeh and Malibu Point. Power plant in Nusa Penida currently consists of a diesel generator in the amount of 19,350 kW (Net Power Capacity) and battery energy storage in the amount of 3,300 kWh. Based on the results of the simulation of the growth of the electricity load using the time series model from the SPSS application, the predicted load will reach 22,806 kW in September 2028. It will potentially cause an electricity deficit, if it is not balanced with an increase in electricity production. The fossil fuels has limited availability and produces emissions. Indonesia has a target of renewable energy mix in the amount of 58-61 percent in 2050 and 70-72 percent in 2060. Therefore, this study provides a choice of power plant composition that can be utilized. The selected power plant are PV, wind turbines, diesel generators, batteries, and converters. From several power plant compositions, one of the best combinations is the PV/WT/BAT/CON. This combination has an NPC value of $152M and an LCOE of 0.152 $/kWh. This study can provide recommendations for companies and governments in meeting the electricity needs of a region and using renewable energy.